THU0072 Prophylactic Treatment with Anti-MIL-21 Ameliorates Disease in Mice with Collagen-Induced Arthritis. (23rd January 2014) - Sandström, C. S.; Hebsgaard, J.; Søndergaard, H.; Lundsgaard, D.; Andersson, E. C.
Abstract : Background: Interleukin 21 (IL-21), a type I cytokine, signals through a composite receptor consisting of a unique private receptor (IL-21R) and the common cytokine receptor γ chain (1 ). The immune-mediated and pro-inflammatory properties of IL-21 suggest that it contributes to the pathogenesis of autoimmune diseases. Previous studies have demonstrated convincingly that IL-21 can trigger inflammatory processes that promote inflammation and joint destruction (2, 3 ). Also, reduced IgG responses in IL-21R-deficient mice demonstrate that the T cell-derived IL-21 is required for the induction of IgG responses (4 ). Objectives: In this study, we examined if blocking of IL-21-mediated processes, by a monoclonal IL-21 antibody, affects disease progression in collagen-induced arthritic mice. Methods: Arthritis was induced at day 0 in DBA/1 mice by an i.d. injection of collagen type II (CII) in complete Freund´s adjuvant followed by an i.d. injection of CII in incomplete Freund´s adjuvant (IFA) at day 21. Mice received an early prophylactic treatment with a monoclonal anti-mouse IL-21 antibody or the corresponding isotype control from day 0 until day 40 (25mg/kg i.p. 3/week). Blockage of TNFα (Etanercept) was used as a standard study control treatment. Throughout the study, mice were assessed three times weekly for clinical symptoms until day 42. Moreover, serum was collected at day 0, 14, 21, 28 and at endpoint (day 42) for analysis of collagen type II-specific antibodies and serum matrix metalloproteinase -3 (MMP-3) levels. Paws from all groups were collected for histopathologic analysis. Results: Early prophylactic treatment with anti-mIL-21 delayed the onset and progression of collagen-induced arthritis. Mice treated with anti-mIL-21 demonstrated a delayed disease onset and a significant reduced clinical score as compared to isotype-treated mice. In addition, at the end of the study, serum levels of both collagen type II-specific antibodies and the disease biomarker MMP-3 were reduced in anti-mIL-21 treated mice as compared to isotype treated mice. Histopathologic analysis revealed a significant lower histology score index in anti-mIL-21 treated mice than in mice treated with the corresponding isotype control and thus confirmed the clinical data. Conclusions: Our findings demonstrate a significant effect of early prophylactic anti-mIL-21 treatment in collagen-induced arthritis. References: Habib T et al. The common gamma chain (gamma c) is a required signalling component of the IL-21 receptor and supports IL-21-induced cell proliferation via JAK3. Biochemistry. 2002 Jul 9;41(27):8725-31. Jüngel A et al. Expression of interleukin-21 receptor, but not interleukin-21, in synovial fibroblasts and synovial macrophages of patients with rheumatoid arthritis. Arthritis Rheum. 2004 May;50(5):1468-76. Monteleone G et al. Interleukin-21 as a new therapeutic target for immune-mediated diseases. Trends Pharmacol Sci. 2009 Aug;30(8):441-447. Ozaki K et al. A critical role for IL-21 in regulating immunoglobulin production. Science. 2002 Nov 22;298(5598):1630-4. Disclosure of Interest: C. Sandström Shareholder of: Minor shareholder, Employee of: contributing scientist, J. Hebsgaard Shareholder of: Minor shareholder, Employee of: Contributing scientist, H. Søndergaard Shareholder of: Minor shareholder, Employee of: Contributing scientist, D. Lundsgaard Shareholder of: Minor shareholder, Employee of: Contributing scientist, E. C. Andersson Shareholder of: Minor shareholder, Employee of: Contributing scientist